Intentions behind common and risky fires in south-eastern Tanzania. Issue 1 (2nd January 2022) - Wood, Ellie; Mgaya, Mercy; Andrews, Christopher; Schreckenberg, Kate; Fisher, Janet A; Grundy, Isla; Ryan, Casey M
Abstract : Human-set fires are a crucial component of African savannas, affecting ecosystem structure, carbon emissions, local hazards and livelihoods. Yet, most fire research in these ecosystems focuses on the fire ecology of protected areas. Research exploring fire regimes in inhabited landscapes remains limited, undermining opportunities for culturally and environmentally sustainable fire management. To address this gap, we used interviews in Tanzanian farming communities and remote sensing to identify intentions behind fire use and the perceived relative frequency and riskiness of fires set for different purposes. We found that the most common ignitions were intentional and important to livelihoods. Burning was adaptive, responsive to environmental conditions, and optimised for the intended outcome with the perceived riskiest fires intentionally spreading uncontrolled. Remote sensing showed that most of the total burned area was accounted for by fires during the late dry season when people burned for activities, such as field preparation, and when environmental conditions encouraged fire spread. Our findings offer an insight into fire regimes in inhabited landscapes, by exploring how intentions shape the fire regime at the landscape scale. We discuss how understanding these intentions and local priorities, including adaptive uses of fire, is key to sustainable fire management outside protected areas.